PRINSIP TINDAK KESANTUNAN VERBAL DAN NON-VERBAL DALAM PERSPEKTIF ISLAM (STUDI INTERDISIPLINER: BAHASA DAN ISLAM) - Muhamad Pahruroji; Pandu Hyangsewu (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
Abstract : Â This study aims to examine how the principles of politeness speak verbally and non-verbally in an Islamic perspective. This research uses a qualitative descriptive approach with the literature study method. The data were obtained from Tafsir Al-Qur'an and Hadith as well as previous studies. The results of the analysis show that in an Islamic perspective there is the concept of language politeness. In the verbal aspect, language politeness is packaged with six qaulan principles which include 1) qaulan sadida, 2) qaulan ma'rufa, 3) qaulan baligha, 4) qaulan maysura, 5) qaulan aliyyin and 6) qaulan karima. Meanwhile, the nonverbal aspect includes body behavior such as shaking hands, cheerful expressions and showing smiles, maintaining eye contact and paralinguistics which includes smooth, low tones or voices, slow intonations and rhythms. Keywords : Politeness, comunicate and islamic perspective